Socioeconomic disparities in physical activity participation: An exploratory study using Malay sample - Cheah, Yong Kang (De La Salle University Publishing House, 2015)
The objective of the present study is to examine the effects of socioeconomic factors on participation in physical activity among Malays in Malaysia.Drawing on a nationally representative sample that contains 17,515 respondents, a logit model is developed to estimate the likelihood of adopting a physically active lifestyle.The results of the present study show that income, age, sex, education, house locality, and employment status are significantly related to the levels of physical activity.In particular, there are negative relationships between higher-income earners, the elderly, females, the less-educated, urban dwellers, and the non-working adults, and the likelihood of being physically active.In view of these findings, several public policies toward promoting physically active lifestyle are proposed.